FAKTOR KONVERSI VOLUME TERHADAP BERAT GAMAL (Gliricidia sepium) BERDASARKAN UMUR TEGAKAN DI SUKABUMI, JAWA BARAT: Volume To Weight Conversion Factors Of Gamal (Gliricidia sepium) Based On Stand Age In Sukabumi, West Java (Jurnal ForestrIndo, 2025)
The conversion factor from stacked wood volume to weight is a widely used method for estimating the biomass of energy plantation forests. However, the general conversion factor for gamal (Gliricidia sepium) established by the Indonesian government does not account for variations in stand age. This study aims to determine age-specific conversion factors for gamal and evaluate the differences in these factors across various stand ages. Field data collection was carried out in a gamal plantation comprising three stand ages—3, 4, and 5 years—located in the Sukabumi Forest Management Unit, West Java. In each stand age, ten gamal trees were felled and grouped based on the similarity in the number of branches to obtain stacked wood samples. A total of 12 stacked wood samples from 30 felled trees were collected across the three stand ages, with their stacked volumes and fresh weights measured to determine conversion factors. The differences in these conversion factors were assessed using the Kruskal-Wallis test. The results indicated conversion factors of 0.286, 0.369, and 0.444 for gamal trees aged 3, 4, and 5 years, respectively. This study confirms that gamal conversion factors differ significantly among stand ages, suggesting the use of age-specific conversion factors would provide accurate estimates of the fresh weight of gamal plantations.Keywords: conversion factor, stand age, gamal, stacked-wood, staple meter